A closed-form solution for the position analysis of a novel fully spherical parallel manipulator – ERRATUM. Issue 5 (11th December 2015) - Enferadi, Javad; Shahi, Amir
Abstract : There was an error in the spelling of the author's affiliation. Where the affiliation read "Department of mechanical engineering, Mashad Branch, Islamic Azad University, Mashad, Iran" it should instead have read "Department of mechanical engineering, Mashhad Branch, Islamic Azad University, Mashhad, Iran". The publisher regrets this error.